2003
DOI: 10.1081/dmr-120023681
|View full text |Cite
|
Sign up to set email alerts
|

PM Frequencies of Major CYPs in Asians and Caucasians

Abstract: Many administered drugs are first activated by phase I drug-metabolizing enzymes, such as cytochrome P450 (CYP), and then conjugated with ligands such as UDPGA, PAPS, and glutathione by phase II drug-metabolizing enzymes, and finally excreted by transporters. There are some defective activity mutants due to CYP polymorphisms. In these cases, drugs are not metabolized [poor metabolizer (PM)], the high drug levels in blood are maintained, and toxic effects appear in the patients. To clarify the ratio of PMs, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
132
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(143 citation statements)
references
References 25 publications
6
132
1
4
Order By: Relevance
“…For Eastern Asians, only 1-2% of individuals have been found to be poor metabolizers (PMs), and approximately 57% of the Chinese population are intermediate metabolizers (IMs) [9,10]. Polymorphic studies have revealed that the IM allele CYP2D6*10 is predominant in Asian populations with frequencies ranging from 30% to 50% [7,11].…”
mentioning
confidence: 99%
“…For Eastern Asians, only 1-2% of individuals have been found to be poor metabolizers (PMs), and approximately 57% of the Chinese population are intermediate metabolizers (IMs) [9,10]. Polymorphic studies have revealed that the IM allele CYP2D6*10 is predominant in Asian populations with frequencies ranging from 30% to 50% [7,11].…”
mentioning
confidence: 99%
“…The low prevalence of mutant genotypes indicates relative infrequency of poor metabolizer in Han Chinese, which is in line with previously reported low-frequency of CYP3A4 poor metabolizer in Asians. 55 Haplotypes of CYP3A4 in Han Chinese Haplotypes were inferred with 11 detected SNPs by the PHASE program. Our reconstruction of haplotypes strengthened previous findings that a few common haplotypes of CYP3A4 occupy a huge proportion of the total chromosomes examined, 54 whereas a large subset of haplotypes carries low levels of variation.…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of CYP2B6*5 is as high as 11% in white and black populations, 3% in Hispanic populations, and 0.3 to 5% in Asian populations (10 -12). CYP2C19*2 is even more frequent at 15 to 17% in white and black patients and up to 30% in Asian patients (12)(13)(14). Patients with these CYP450 variants may be It is likely that both approaches will be used in combination to generate personalized medicine panels to individualize therapies.…”
Section: Therapy Based On Genetic Variants In Drug Metabolic Pathwaysmentioning
confidence: 99%